Analysis of the effects of porous media parameters and inclination angle on the thermal storage and efficiency improvement of a photovoltaic-phase change material system. (June 2022) - Variji, Nazanin; Siavashi, Majid; Tahmasbi, Milad; Bidabadi, Mehdi
Abstract: The heat generation in the photovoltaic (PV) panels leads to the rise in temperature, which subsequently deteriorates the electrical efficiency of PV panels. The application of phase change materials (PCM) can reduce the operating temperature and perform as a cooling mechanism. However, the cooling performance and energy storage capacity of PCM are drastically affected by its poor thermal conductivity. Therefore, in this paper, the impact of the insertion of metal foam on the heat transfer through PCM and the electrical efficiency of PV-PCM systems has been numerically investigate. A comparative study on the impact of the porosity of metal foam ranging from 0.7 to 0.9 has been carried out. Furthermore, different inclination angles, 0° to 90°, have been considered to evaluate the impact of inclination angle on the natural convection enhancement through liquid PCM. Results indicated that increasing the inclination angle results in better natural convection of molten PCM and better heat transfer through PCM. Moreover, results represented that compared with the PV-PCM system, 6.8% and 9.8% enhancement in the average temperature and electrical efficiency, in the case of insertion of metal foam with porosity of 0.9, is achieved. Highlights: Energy storage with PCM used below PV panels is studied in presence of metal foam. Metal foam and inclination angle effects on PV efficiency & PCM energy storage are studied. Increment of inclination angle improves the efficiency. Using high porosity metal foams enhances the PCM conductivity and melting time. Using metal foams causes reduction in thermal storage capacity.